1997
DOI: 10.1111/j.1469-7793.1997.187bi.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of Carotid Chemoreceptor Dynamic and Steady‐State Sensitivity to CO2 in the Newborn Lamb

Abstract: The maturation of carotid chemoreceptor steady‐state and dynamic responses to CO2 in newborn lambs was measured. In total, sixteen fibres (13 lambs) were studied at 3–4 days, nineteen fibres (13 lambs) at 5–9 days and twenty‐one fibres (17 lambs) at 10–24 days after birth. Steady‐state CO2 sensitivity was measured over a range of arterial CO2 pressures (Pa,CO2) at four levels of arterial O2 pressure (Pa,O2): hyperoxia (Hyp), 115–150 mmHg; normoxia (Nx), 90–105 mmHg; moderate hypoxia (ModHx), 40–60 mmHg; and se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
12
1
1

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 23 publications
2
12
1
1
Order By: Relevance
“…This positive interaction has been confirmed in recent studies carried out on goats, lambs, piglets, cats, rats, and mice (Daristotle et al 1987;Wolsink et al 1992;Carroll et al 1993;Tankersley et al 1994Tankersley et al , 2004Pepper et al 1995;Calder et al 1997), although some early studies showed a negative interaction in cats (Ou et al 1976). We compared the ventilatory response to hypoxic hypercapnia between CS-and FA-exposed mice.…”
Section: Chronic Cs Exposure Produced An Abnormal Inhibitory Interactsupporting
confidence: 54%
“…This positive interaction has been confirmed in recent studies carried out on goats, lambs, piglets, cats, rats, and mice (Daristotle et al 1987;Wolsink et al 1992;Carroll et al 1993;Tankersley et al 1994Tankersley et al , 2004Pepper et al 1995;Calder et al 1997), although some early studies showed a negative interaction in cats (Ou et al 1976). We compared the ventilatory response to hypoxic hypercapnia between CS-and FA-exposed mice.…”
Section: Chronic Cs Exposure Produced An Abnormal Inhibitory Interactsupporting
confidence: 54%
“…The CO 2 response of the isolated carotid body is present in young animals and generally equal to the adult response. The multiplicative interaction between hypercapnia and hypoxia increases over the course of development, but the intrinsic CO 2 sensitivity of the carotid body under normoxic conditions does not vary much as a function of age (Pepper et al, 1995;Calder et al, 1997;Bamford et al, 1999). The contribution of peripheral chemoreceptors to the normoxic hypercapnic ventilatory response in intact animals is stable in the neonatal period of development in humans as well, but the interactive effects of CO 2 -O 2 at the carotid body seem to increase as babies mature (Søvik and Lossius, 2004).…”
Section: Differential Maturation Between Peripheral Versus Central Chmentioning
confidence: 95%
“…Preterm infants displayed an age-related increase in steady-state CO 2 sensitivity (10, 11), whereas term infants showed no such postnatal development (12, 13). Dynamic CO 2 sensitivity was unchanged during the first month in neonatal lambs (8,14), whereas in piglets the relative contribution of peripheral chemoreceptors to CO 2 stimulation increased postnatally (15).Ultimately, the combined effects of PCO 2 , arterial PO 2 , and pH determine the level of ventilation. Nonlinear interaction between PCO 2 and PO 2 , i.e.…”
mentioning
confidence: 99%
“…Nonlinear interaction between PCO 2 and PO 2 , i.e. increased CO 2 chemosensitivity at increasing levels of hypoxia, has been described in carotid and aortic nerve recordings (7,8,16) and in ventilatory responses in animals (17, 18) and adult humans (19). Whether interaction between PCO 2 and PO 2 is present at birth and whether it increases postnatally differs from one species to another (7,16,20 …”
mentioning
confidence: 99%